Hidroxiapatita sintetizada a partir de la cáscara de huevo como potencial sustituto óseo en defectos periodontales y periimplantarios - Camacho Díaz, Isabel (2018)
Synthetic hydroxyapatite is a biomaterial widely used in guided bone regeneration procedures. Objective: Synthesize synthetic hydroxyapatite from eggshells under different precipitates of nitric acid. Methods: Experimental study, which obtained CaCO3 from the pulverization of eggshells (Gallus gallus). The carbonate was titrated with three concentrations of nitric acid (5, 10 and 15%) and ammonium phosphate. The mixtures were tested at different calcination temperatures (150, 600, 700, 800 and 900 °C) and calcination times (2, 4, 8 and 12 h). X-ray diffraction analysis was used to characterize the presence of calcium carbonate and hydroxyapatite. Results: Of the different routes of synthesis, the route of precipitation of nitric acid by excess to 15% plus calcined calcium carbonate at 700 °C during 8h offered more equivalent results to the synthetic hydroxyapatite when compared with the commercial standard. The peaks of intensity corresponded to the angles 2θ: 20, 26, 33, 34, 40, 48 and 50. Conclusions: The method of synthesis by precipitation, using calcium carbonate from eggshells as substrate plus calcium nitrate and nitric acid; proved to be adequate and practical for the synthesis of hydroxyapatite. Its use can be replicated for toxicological characterization and response studies in pre-clinical experimental models.